Integrated transcriptomic hypothalamic-pituitary-ovarian axis network analysis reveals the role of energy availability on egg production in layers - Jianling Peng; Yong Cui; Haiping Liang; Shenyijun Xu; Linjian Weng; Meng Ru; Ramlat Ali; Qing Wei; Jiming Ruan; Jianzhen Huang (Animal Nutrition)
Energy is a crucial component for maintaining egg production in layers. The hypothalamic-pituitary-ovarian (HPO) axis is an energy-sensitive functional axis for follicle development, synthesis, and secretion of reproductive hormones, and plays a key role in modulating sustained ovulation in layers. To investigate the mechanism of integrated network regulation of the HPO axis under energy fluctuation, ninety Hy-line brown layers (265-day-old, 1.92 ± 0.02 kg) were randomly divided into three groups for a 17-day experiment: a control group (Con group) fed ad libitum from days 1 to 17, an energy-deprived group (ED group) that was fed ad libitum from days 1 to 12 and then underwent a fasting period from days 13 to 17 to induce a pause in laying, and a re-fed group (Rf group) that fasted for seven days (specifically, days 1 to 5, day 7, and day 9), had ad libitum access to feed on days 6 and 8, and was continuously fed from days 10 to 17. Each treatment consisted of 10 replicates with 3 birds per replicate. The study found that energy deprivation significantly decreased reproductive performance such as egg laying rate, ovarian index, number of small yellow follicles (SYF), and normal hierarchical follicles (NHIE) (P < 0.05), which recovered after refeeding, indicating the importance of energy availability for sustained ovulation in layers. In addition, estradiol (E2), estradiol to progesterone (E2/P4) ratio, and luteinizing hormone (LH) displayed changes similar to follicle number, whereas follicle-stimulating hormone (FSH) exhibited a contrasting pattern. Transcriptome analysis revealed that energy deprivation downregulated genes related to energy and appetite-regulated neurotransmitter receptors and neuropeptides in the hypothalamus. These signals combined to inhibit gonadotropin-releasing hormone (GnRH) secretion and subsequently downregulated the crucial genes responsible for synthesizing gonadotropins, gonadotropin-releasing hormone receptor (GnRHR), and glycoprotein hormones alpha chain (CGA). Consequently, this suppression of the hypothalamus and pituitary affected ovarian function through ovarian steroidogenesis and the extracellular matrix (ECM)-receptor interaction. These findings suggest that energy deprivation inhibits the function of the HPO axis, leading to impaired follicle development and reduced egg production, and that refeeding can partially restore these indicators.